If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7(3x + -3) = 22x Reorder the terms: 7(-3 + 3x) = 22x (-3 * 7 + 3x * 7) = 22x (-21 + 21x) = 22x Solving -21 + 21x = 22x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-22x' to each side of the equation. -21 + 21x + -22x = 22x + -22x Combine like terms: 21x + -22x = -1x -21 + -1x = 22x + -22x Combine like terms: 22x + -22x = 0 -21 + -1x = 0 Add '21' to each side of the equation. -21 + 21 + -1x = 0 + 21 Combine like terms: -21 + 21 = 0 0 + -1x = 0 + 21 -1x = 0 + 21 Combine like terms: 0 + 21 = 21 -1x = 21 Divide each side by '-1'. x = -21 Simplifying x = -21
| 3x+120=5x+132 | | 6x^2-25x-25=0 | | 4c=-16 | | 5y+8=7y-6 | | x+x+x+1=x+4 | | 4x+9=-75 | | 7x+194+5x+70=180 | | 7x+194=5x+70 | | -(8y+4)-(-7y-7)=1 | | 4y-8+y+58=5y+50-2y | | 6x+13+4x+87=180 | | x^2+24x+44=0 | | 6x+13=4x+87 | | 4(3x-1)=-13 | | 2(t-4)+6t=4(2t+3)-11 | | 9+4d=29 | | 4x^2+12x=-7 | | 10x=8x+6 | | c+9=11 | | 2x+34=4x+8 | | 4(3x-3)=2(6x+8) | | 2(t-4+6t)=4(2t+3)-11 | | 2(x+11)=6x-4 | | 6+5m=16 | | 4(3x+7)= | | 4x+48=7x+24 | | 4x+48+7x+24=180 | | 3+16z-2=7z+97-3z | | 25x+25x+15x+12+15x+12= | | 4(3x-1)=13 | | 12x+28= | | 2x+62=4x+22 |